Methane Inhibition Alters the Microbial Community, Hydrogen Flow, and Fermentation Response in the Rumen of Cattle - Martinez-Fernandez, Gonzalo; Denman, Stuart E.; Yang, Chunlei; Cheung, Jane; Mitsumori, Makoto; McSweeney, Christopher S. (Frontiers in Microbiology, 2016)
Management of metabolic hydrogen ([H]) in the rumen has been identified as an important consideration when reducing ruminant CH4 emissions. However, little is known about hydrogen flux and microbial rumen population responses to CH4 inhibition when animals are fed with slowly degradable diets. The effects of the anti-methanogenic compound, chloroform, on rumen fermentation, microbial ecology and H2 /CH4 production were investigated in vivo. Eight rumen fistulated Brahman steers were fed a roughage hay diet (Rhode grass hay) or roughage hay:concentrate diet (60:40) with increasing levels (low, mid and high) of chloroform in a cylcodextrin matrix. The increasing levels of chloroform resulted in an increase in H2 expelled as CH4 production decreased with no effect on dry matter intakes. The amount of expelled H2 per mole of decreased methane, was lower for the hay diet suggesting a more efficient redirection of hydrogen into other microbial products compared with hay:concentrate diet. A shift in rumen fermentation towards propionate and branched-chain fatty acids was observed for both diets. Animals fed with the hay:concentrate diet had both higher formate concentration and H2 expelled than those fed only roughage hay. Metabolomic analyses revealed an increase in the concentration of amino acids, organic and nucleic acids in the fluid phase for both diets when methanogenesis was inhibited. These changes in the rumen metabolism were accompanied by a shift in the microbiota with an increase in Bacteroidetes:Firmicutes ratio and a decrease in Archaea and Synergistetes for both diets. Within the Bacteroidetes family, some OTUs assigned to Prevotella were promoted under choloroform treatment. These bacteria may be partly responsible for the increase in amino acids and propionate in the rumen. No significant changes were observed for abundance of fibrolytic bacteria, protozoa and fungi, which suggests that fibre degradation was not impaired. The observed 30% decrease in methanogenesis did not adversely affect rumen metabolism and the rumen microbiota was able to adapt and redirect [H] into other microbial end-products for both diets. However, it is also required dietary supplements or microbial treatments to capture the additional H2 expelled by the animal to further improve rumen digestive efficiency.